Guillain-Barré Syndrome and Miller Fisher Syndrome in Association With an Arboviral Outbreak: A Brazilian Case Series - do Rosário, Mateus Santana; de Jesus, Pedro Antônio Pereira; Farias, Daniel Santana; Novaes, Marco Antônio Caires; Francisco, Marcos Vinicius Lima Oliveira; Santos, Cleiton Silva; Moura, Daniel; Lima, Fernanda Washington de M.; Alcantara, Luiz Carlos Junior; de Siqueira, Isadora Cristina (Frontiers in Medicine, 2022)
Introduction Guillain-Barré syndrome (GBS) in association with arboviruses, such as Zika, chikungunya, and dengue, has been previously documented; however, Miller-Fisher Syndrome (MFS) and other GBS subtypes are rarely reported. Methods We identified a series of GBS and MFS cases that were followed during the Zika virus outbreak in Salvador, Brazil (2015–2016). Blood and CSF samples were collected for virus diagnosis. In addition, serological studies to verify previous arboviral infection and electromyography (EMG) were performed. Results Of the 14 patients enrolled, 10 were diagnosed with GBS, including three GBS subtypes (two cases of bifacial weakness with paresthesia and one case of paraparetic GBS), and four as MFS. IgM antibodies against one or more of three arboviruses were present in 11 (78.6%) patients: anti-zika IgM positivity in eight (57%), anti-Chikungunya IgM in three (21%), and anti-Dengue in one (7%) individual. A single case was positive for both anti-Dengue IgM and anti-Chikungunya IgM, suggesting co-infection. EMG revealed an AIDP pattern in all nine patients analyzed. Conclusion The current case series contributes to our knowledge on the clinical presentation of arbovirus-associated GBS and its subtypes, including MFS, and serves as an alert to clinicians and other healthcare professionals in regions affected by arbovirus outbreaks. We highlight the importance of recognizing arboviruses in diagnosing GBS and its subtypes.